2007
DOI: 10.2337/db06-1051
|View full text |Cite
|
Sign up to set email alerts
|

Association Studies of BMI and Type 2 Diabetes in the Neuropeptide Y Pathway

Abstract: The neuropeptide Y (NPY) family of peptides and receptors regulate food intake. Inherited variation in this pathway could influence susceptibility to obesity and its complications, including type 2 diabetes. We genotyped a set of 71 single nucleotide polymorphisms (SNPs) that capture the most common variation in NPY, PPY, PYY, NPY1R, NPY2R, and NPY5R in 2,800 individuals of recent European ancestry drawn from the near extremes of BMI distribution. Five SNPs located upstream of NPY2R were nominally associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 50 publications
1
37
0
1
Order By: Relevance
“…The earlier genetic and epidemiological studies indicate that the NPY Leu7Pro allele is a major risk factor for obesity (Ding et al, 2005;van Rossum et al, 2006). In Table 2 NPY gene polymorphisms and obesity (Campbell et al, 2007). Ding (2003) reported that the Pro7 allele might have originated in the north of Europe and then spread to the neighboring regions, and the frequency showed a decreasing north to south gradient and also stated that the highest allele frequencies were found in the Nordic countries.…”
Section: Discussionmentioning
confidence: 99%
“…The earlier genetic and epidemiological studies indicate that the NPY Leu7Pro allele is a major risk factor for obesity (Ding et al, 2005;van Rossum et al, 2006). In Table 2 NPY gene polymorphisms and obesity (Campbell et al, 2007). Ding (2003) reported that the Pro7 allele might have originated in the north of Europe and then spread to the neighboring regions, and the frequency showed a decreasing north to south gradient and also stated that the highest allele frequencies were found in the Nordic countries.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Prioritizer predicted the NPY2R gene as being associated with obesity and T2D [Elbers et al, 2007], and a few months later Campbell et al published an article stating they had found association of NPY2R with both traits in 2,800 Caucasian individuals [Campbell et al, 2007].…”
Section: Network Analysesmentioning
confidence: 99%
“…Assays were multiplexed up to a maximum of five using the homologous Mass Extension (hME) protocol (Gabriel et al 2002;Campbell et al 2007). The iPLEX protocol was used to multiplex assays up to a maximum of 25 as follows.…”
Section: Replicatedmentioning
confidence: 99%